Antonio López García's everyday urban worlds : a philosophy of painting - Fraser, Benjamin (Fairleigh Dickinson University Press, 2014)
This book carries the reader on an interdisciplinary journey through painting, philosophy, art criticism, Spanish literature and film, history and culture, immigration, architecture, urban planning, and more. Made for general readers and with endnotes appealing to the specialist, each chapter is inspired by a single image by the Spanish artist.